2009
DOI: 10.1002/jcp.21802
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell‐derived neurotrophic factor increases migration of human chondrosarcoma cells via ERK and NF‐κB pathways

Abstract: Invasion of tumor cells is the primary cause of therapeutic failure in the treatment of malignant chondrosarcomas. Glial cell-derived neurotrophic factor (GDNF) plays a crucial role in migration and metastasis of human cancer cells. Integrins are the major adhesive molecules in mammalian cells. Here we found that GDNF directed the migration and increased cell surface expression of alphav and beta3 integrin in human chondrosarcoma cells. Pretreated of JJ012 cells with MAPK kinase (MEK) inhibitors PD98059 or U01… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…Recently, our and other reports have shown that NF-kB signaling pathway play a key role of cancer cell motility in response to growth factors and adipokines [Huang et al, 2007;Su et al, 2009;Tan et al, 2009;Tang and Lu, 2009; Lu et al, 2010a,b]. The results of this study showed that NF-kB activation contributes to ghrelin-induced glioma cell migration, and that the inhibitors of the NF-kB dependent signaling pathway.…”
Section: Ghrelin Induces Migration In Glioma Cellssupporting
confidence: 51%
“…Recently, our and other reports have shown that NF-kB signaling pathway play a key role of cancer cell motility in response to growth factors and adipokines [Huang et al, 2007;Su et al, 2009;Tan et al, 2009;Tang and Lu, 2009; Lu et al, 2010a,b]. The results of this study showed that NF-kB activation contributes to ghrelin-induced glioma cell migration, and that the inhibitors of the NF-kB dependent signaling pathway.…”
Section: Ghrelin Induces Migration In Glioma Cellssupporting
confidence: 51%
“…Increased levels of GDNF in the urine could serve as a basis for the adjunct diagnosis, monitoring, and treatment of interstitial cystitis in patients with bladder cancer (Okragly et al 1999). Recently, we reported that GDNF increases cell migration and metastasis in gliomas, chondrosarcomas, and oral squamous cell carcinomas (Su et al 2009, Lu et al 2010, Chuang et al 2013. Moreover, it has also been reported that the GDNF expression in colon adenocarcinoma cells may play an important role in the pathogenesis of intestinal ganglioneuromatosis (Qiao et al 2009), where an increased expression of GDNF is associated with diffuse ganglioneuromatosis (Furuta et al 2007).…”
Section: Introductionmentioning
confidence: 93%
“…The different MAPKs can be divided into 3 main subgroups, that is, the extracellular signal-regulated protein kinase (ERK), c-Jun N-terminal kinase/ stress-activated protein kinases (JNK/SAPK), and p38 (9). MAPKs are commonly activated through phosphorylation cascades, and subsequently phosphorylate a number of effectors that contribute to the regulation of diverse cellular events, including differentiation (10,11), proliferation (12,13), survival (14), migration (15), and invasion (16). MAPK kinase kinase kinase isoform 4 (MAP4K4), a germinal centre protein kinase that belongs to the mammalian STE20/MAP4K family, is implicated in the activation of the JNK/SAPK pathway (17,18).…”
Section: Introductionmentioning
confidence: 99%